Equity and diversity in the nephrology workforce in Australia and New Zealand. Issue 11 (3rd June 2022) - Francis, Anna; O'Sullivan, Kim M.; Patel, Pinika; Viecelli, Andrea K.; Hedley, James A.; Swaminathan, Ramyasuda; Crosthwaite, Amy; Haloob, Imad; Kennard, Alice; Rowlandson, Matthew; Boudville, Neil; Webster, Angela C.; et al.
Abstract: Background: Despite diversity initiatives, inequities persist in medicine with negative implications for the workforce and patients. Little is known about workplace inequity in nephrology. Aim: To describe perceptions and experiences of bias by health professionals in the Australian and New Zealand Society of Nephrology (ANZSN), focussing on gender and race. Methods: A web‐based survey of ANZSN members recorded degree of perceived inequity on a Likert scale, ranging from 1 (none) to 5 (complete). Groups were compared using Mann–Whitney U ‐test and logistic regression. Comments were synthesised using qualitative methods to explore themes of inequity and pathways to an inclusive future. Results: Of the 620 members of the ANZSN, there were 134 (22%) respondents, of whom 57% were women and 67% were White. The majority (88%) perceived inequities in the workforce. Perceived drivers of inequity were gender (84/113; 75%), carer responsibilities (74/113; 65%) and race (64/113; 56%). Half (74/131) had personally experienced inequity, based on gender in 70% (52/74) and race in 39% (29/75) with perceived discrimination coming from doctors, patients, academics and health administrators. White males were least likely (odds ratio 0.39; 95% confidence interval 0.18–0.90) to experience inequity. Dominant themes from qualitative analysis indicated that the major impacts of inequity were limited opportunities for advancement and lack of formal assistance for those experiencing inequities. Proposed solutions to reduce inequity included normalising the discourse on inequity at an organisational level, with policy changes to ensure diverse representation on committees and in executive leadership positions. Conclusions: Inequity, particularly driven by gender and race, is common for nephrology health professionals in Australia and New Zealand and impacts career progression.